Regional distribution of chemical tracers in snow cover along the route from S16 to Dome Fuji Station, east Dronning Maud Land, Antarctica - スズキ, トシタカ; イイズカ, ヨシノリ; フルカワ, テルオ; マツオカ, ケンイチ; カミヤマ, コキチ; ワタナベ, オキツグ; Suzuki, Toshitaka; Iizuka, Yoshinori; Furukawa, Teruo; Matsuoka, Kenichi; Kamiyama, Kokichi; Watanabe, Okitsugu (National Institute of Polar Research, 2001)
P(論文) We show and discuss the regional distributions of Cl^-, Na^+, SO_4^2,NO_3 and ^7Be concentrations in snow cover along the route from S16 to Dome Fuji Station in east Dronning Maud Land, Antarctica. The concentrations of Cl and Na^+ at the coast exponentially decreased with distance from the coast up to 200km inland. Between 200-1000km inland, the concentrations of Na^+ were nearly constant. On the other hand, the concentrations of Cl increased with distance beyond 750km inland. Furthermore, the contribution factors between Cl and Na^+ decreased and the Cl/Na^+ ratio and the nssCl^-/Cl^- ratio increased toward the interior of the continent. These results indicate that sea salt aerosols are transported from the coastal region toward the inland region of the Antarctic continent, and that a source of Cl other than sea salt exists in the inland plateau of Antarctica. The concentrations of SO_4^2,NO_3 and ^7Be in snow were relatively high in the coastal region and the inland plateau region compared with those in the katabatic-wind region. departmental bulletin paper